CRIMINAL LIABILITY UNDER ART. 110-2 OF THE CRIMINAL CODE OF UKRAINE «FINANCE OF ACTIONS COMMITTED WITH THE PURPOSE OF FORCING CHANGE OR OVERTHROW OF THE CONSTITUTIONAL ORDER OR CAPTURE OF STATE AUTHORITY, CHANGES OF TERRITORY BOUNDARIES OR THE STATE BOR - Lysko, Tetyana; Makoznak, Sofiya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to analyze the financing of actions committed with the aim of violent change or overthrow of the constitutional order or seizure of state power, change of the boundaries of the territory or state border of Ukraine (Article 110-2 of the Criminal Code of Ukraine). Research methods: a combination of general (analysis, synthesis, comparison, induction, deduction) and special research methods (systemic-functional, formal-logical, formal-legal) are applied. The author identifies the essential features inherent in this crime and makes a comparative analysis of the financing of such actions with other corpus delicti provided for in the Criminal Code of Ukraine. Results: the problematic aspects of using the concept of «separatism» in criminal law research. The purpose is to determine the nature and nature of financing of actions committed with the aim of violent change or overthrow of the constitutional order or seizure of state power, change of the boundaries of the territory or state border of Ukraine (hereinafter - financing of actions). Changes in public life entail changes in criminal law. The requirements of today, the conflict between the need to effectively counteract terrorist and separatist phenomena in the country and the requirements for liberalization of legislation put forward by the European Union, prompt constant work on criminal and criminal procedure legislation. Discussion: to study criminal liability for financing actions committed with the aim of violent change or overthrow of the constitutional order or seizure of state power, change of the boundaries of the territory or state border of Ukraine (Article 110-2 of the Criminal Code of Ukraine);to define the most commonly used legal concepts regarding the crime under Article 110-2 of the Criminal Code of Ukraine; to determine the formats of financing the crime under Article 110-2 of the Criminal Code of Ukraine; to identify the problematic aspects of law enforcement practice under Article 110-2 of the Criminal Code of Ukraine; to develop, on the basis of the above, scientifically based recommendations on the qualification of acts on the grounds of the crime under Article 110-2 of the Criminal Code of Ukraine.